Computational Analysis of Queues with Catastrophes in a Multiphase Random Environment. (3rd August 2016) - Vinodhini, G. Arul Freeda; Vidhya, V.
Abstract : A dynamically changing road traffic model which occasionally suffers a disaster (traffic collision, wrecked vehicles, conflicting weather conditions, spilled cargo, and hazardous matter) resulting in loss of all the vehicles (diverted to other routes) has been discussed. Once the system gets repaired, it undergoesn - 1 trial phases and finally reaches its full capacity phase n . We have obtained the explicit steady state probabilities of the system via Matrix Geometric Method. Probability Generating Function is used to evaluate the time spent by the system in each phase. Various performance measures like mean traffic, average waiting time of vehicles, and fraction of vehicles lost are calculated. Some special cases have also been discussed.